2004
DOI: 10.1089/104454904323090912
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Drugs Inhibit MMP-9 Activity from Human THP-1 Macrophages

Abstract: It is now recognized that atherosclerosis complications are related to the unstable character of the plaque rather than its volume. Vulnerable plaques often contain a large lipid core, a reduced content of smooth muscle cells, and accumulation of inflammatory cells. Colocalization of macrophages and active matrix metalloproteinases (MMPs) is likely relevant for atherosclerotic lesion disruption. Nevertheless, MMP activity and regulation by cardiovascular drugs remains poorly defined. In this study, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Since CLAs are PPARγ ligands and known to inhibit NF-κB-mediated expression of pro-inflammatory genes via PPARγ in various cell lines [15,16], we studied whether CLA isomers are capable of affecting gene expression and gelatinolytic activity of MMPs in macrophages which have not yet been investigated. As a model system we used the well-established PMA-differentiated THP-1 macrophage cell model, which is widely used to investigate the effects of compounds on macrophage MMP gene expression and activity [20,35,36]. In addition, several studies dealing with CLA have used the THP-1 macrophage cell model [18,26,37].…”
Section: Discussionmentioning
confidence: 99%
“…Since CLAs are PPARγ ligands and known to inhibit NF-κB-mediated expression of pro-inflammatory genes via PPARγ in various cell lines [15,16], we studied whether CLA isomers are capable of affecting gene expression and gelatinolytic activity of MMPs in macrophages which have not yet been investigated. As a model system we used the well-established PMA-differentiated THP-1 macrophage cell model, which is widely used to investigate the effects of compounds on macrophage MMP gene expression and activity [20,35,36]. In addition, several studies dealing with CLA have used the THP-1 macrophage cell model [18,26,37].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by studies demonstrating PPARα expression in cells of the vessel wall, including endothelial cells [3], smooth muscle cells [4] and macrophages [5]. Furthermore, in vitro studies have demonstrated that fibrates reduce a variety of mediators implicated in atherosclerotic plaque development, including proteins involved in cell recruitment [6], cell adhesion [7], cell migration [8], foam cell formation [9] and plaque stability [10]. In addition, polymorphisms in the PPARα gene have been linked to alterations in the risk of cardiovascular disease in the absence of changes in lipid levels [11].…”
Section: Introductionmentioning
confidence: 88%
“…All media contained L-glutamine supplemented with penicillin (100 U/ml)/ streptomycin (100 lg/ml), and 10% (v/v) heatinactivated fetal bovine serum (FBS) in a humidified atmosphere of 5% CO 2 and 95% O 2 at 37°C. To induce monocyte differentiation into macrophage, the THP-1 monocytes were treated with PMA (400 ng/ml) for 72 h, before Wy-14643, Gyp-XLIX or vehicle (0.1% DMSO) were added, and incubated for a further 48 h in culture medium for the macrophage treatment experiments [18]. The HUVEC cells were grown in M199 medium (Invitrogen Australia) supplemented with 20% FBS, 50 lg/ml endothelial cell growth supplement (Sigma, Australia), 25 mM Hepes buffer, 2 mM L-glutamine, 100 U/ml penicillin, and 100 U/ml streptomycin.…”
Section: Cell Culturementioning
confidence: 99%
“…Whereas Gyp-XLIX effectively enhanced PPARa luciferase activity, it showed minimal effects on PPAR-b=d and -c1 luciferase activity, even at high concentrations (Figure 7a). To further confirm this selectivity for PPAR-a, THP-1 derived macrophage, a cell line endogenously expressing the three PPAR isoforms [18,39], was employed mRNAs and protein were extracted from the cells and examined by RT-PCR and immunoblotting, respectively. Treatment for 48 hours with vehicle (DMSO), Gyp-XLIX and the respective positive controls for PPAR-a (Wy-14643, 50 lM), PPARb=d (bezafibrate, 100 lM) and PPAR-c (ciglitazone, 10 lM), showed comparable profiles in both PPAR-a mRNA (Figure 7b) and protein (Figure 7c) expression, with minimal or no significant increase in mRNA and protein expression for PPAR-b=d and -c.…”
Section: Effects Of Gp Extract and Gyp-xlix On Ppar-a In Cell Linesmentioning
confidence: 99%